The Importance of Otoneurological Evaluation in Brazilian Workers Exposed to Pesticides: A Preliminary Study - Zeigelboim,Bianca Simone (2019)
Abstract Introduction Agrochemicals, also known as pesticides, are widely used in agriculture and in public health. They are organic and inorganic chemical substances with a high level of toxicity not only for the environment, but also for human health. Objective To verify findings on labyrinthine assessment in endemic disease control agents, and to recommend the inclusion of the vestibular exam in the set of tests for pesticide-exposed populations. Methods Descriptive, prospective, cross-sectional study with a sample comprising 15 endemic disease control agents, males,mean age of 51.6 years old (standard deviation [SD] = 5.9). All of the participants were submitted to anamnesis, otorhinolaryngological screening, and vestibular assessment. Results Regarding the most reported complaints, dizziness (73.4%), headache (60%), and tingling in the extremities (53.4%) were observed. The findings of the vestibular exams were normal in 53.3%, while 46.7% showed peripheral vestibular disorder, of which 26.7% were of deficitary type, and 20% of the irritative type. Conclusions Alteration in the vestibular system was verified in 50% of the workers, with a greater prevalence in the caloric testing. Several disorders related to pesticides intoxication are scientifically known. Actions promoting knowledge and qualification of this population for the proper handling of chemicals are suggested, in addition to the elaboration and inclusion of protocols of vestibular assessment in hearing health programs for the prevention, diagnosis and treatment of vestibular disorders.